Experimental investigation of an automotive air conditioning system using R444A and R152a refrigerants as alternatives of R134a - Direk, Mehmet (Strojniški vestnik, 2019)
The conventional refrigerants used in refrigeration systems cause global warming effect if released into the atmosphere. To overcome this problem, refrigerants are classified according to their global warming potential (GWP) values, and some restrictions have been placed on the use and transport of these refrigerants with European regulations. Vapor compression refrigeration (VCR) systems are used to provide desired conditions in many systems and as well as in automobiles. Most of the automotive air conditioning (AAC) systems use R134a which has GWP value of 1300. In this study, the use of the refrigerants which have low GWP values, namely, R152a and R444A as an alternative to the R134a for AAC systems, were investigated experimentally. Moreover, the effect of a plate-type internal heat exchanger (IHX) added into the system was studied with the refrigerant R444A. The cooling capacity, compressor power, coefficient of performance (COP) and total exergy destruction have been determined as performance parameters. Based on the obtained results, the highest COP and cooling capacity were achieved when the R152a used as the refrigerant. Furthermore, the COP of the system was increased when the IHX was used, with R444A as the refrigerant.
Keywords: alternativna hladilna sredstva; automotive air conditioning; coefficient of performance; mobilne klimatske naprave; R134a; R152a; R444A; vrednost hladilnega števila